N-β-Glycosyl sulfamides are selective inhibitors of the cancer associated carbonic anhydrase isoforms IX and XII - Rodríguez, Oscar Mariano (2011)
The transmembrane isoforms of carbonic anhydrase (CA IX and XII) have been shown to be linked to carcinogenesis and their inhibition to arrest primary tumor and metastases growth. In this Letter, we present a series of peracetylated and deprotected N-β-glycosyl sulfamides that were tested for the inhibition of 4 carbonic anhydrase isoforms: the cytosolic hCA I and hCA II and transmembrane tumor-associated IX and XII. Compounds 1–4 and 6–8 selectively target cancer-associated CAs (IX and XII) with KIs in the low nanomolar range.